English Language Teachers’ Experience of Virtual Class during COVID-19 Lockdown in Bhojpur: A Narrative Inquiry (Journal of NELTA, 2022)
This research aimed at exploring English teachers’ experience of virtual class in the time of COVID-19 lockdown period in Bhojpur, Nepal. Using narrative inquiry as methodological lens, I collected four secondary level English language teachers’ stories during the ﬁrst lockdown phase. In-depth interview was conducted to enable the participants to reveal their individual experiences of virtual teaching. The ﬁ ndings revealed negative experiences such as technology related anxiety and mental stress being the absent of basic mastery of ICT in English teachers. The narrations further showed unstable electricity and low speed internet issue, low rate of students’ absence, unavailability of ICT devices as the obstacles fronted by English teachers in the district. The result also displayed positive experiences such as the increase of knowledge and skills in ICT use, and students’ autonomous and mobile learning.